Rosmarinic acid as pancreatic lipase inhibitor - Raja Abd. Rahman, Raja Noor Zaliha; Alias, Norsyuhada; Mohamad Ali, Mohd. Shukuri; Leow, Adam Thean Chor (2016)
The present invention pertains to rosmarinic acid for use in the inhibition of pancreatic lipase. The use of the present invention may be applied in medical and dietary methods for the reduction of body fat in mammals. The invention is in particular useful for the treatment of metabolic disorders such as obesity or diabetes.